(untitled) (The Research of Medical Science Review, 2025)
Objectives: To evaluate the feasibility, safety, and effectiveness of retrograde intrarenal surgery (RIRS) as a day care procedure, focusing on perioperative complications, stone clearance rates, and factors influencing same-day discharge. Methods: A retrospective, single-center study conducted from September 2018 to September 2024 included 260 patients aged 18+ who underwent RIRS with planned same-day discharge. The outcomes analyzed included discharge success, perioperative complications, and stone clearance. Demographics, clinical parameters, and surgical details were compared between feasible and non-feasible groups using statistical tests. Results: Day care surgery was feasible in 189 (72.7%) patients, while 71 (27.3%) required extended care. The feasible group had significantly lower BMI (22.00 ± 5.0 vs. 24.00 ± 5.0, p = 0.018), smaller stones (1.25 ± 0.6 cm vs. 1.50 ± 1.0 cm, p = 0.027), lower pre-operative creatinine (0.90 ± 0.2 vs. 1.00 ± 0.5 mg/dL, p < 0.001), and lower hematocrit (35.80 ± 5.10% vs. 38.09 ± 5.87%, p = 0.002). Logistic regression identified larger stone size (OR = 2.521, p = 0.004), male gender (OR = 2.595, p = 0.023), and UTIs as significant predictors of feasibility. Post-operative complications were lower in the feasible group (99.5% vs. 54.9%, p < 0.001). Conclusion: RIRS is a feasible and safe day care procedure for selected patients, with high success rates, minimal complications, and effective stone clearance, offering a viable alternative to traditional hospitalization.